HUKUM DAN STRATEGI PENYELESAIAN UTANG - PIUTANG MURABAHAH PADA PERBANKAN DAN LEMBAGA KEUANGAN SYARIAH - Suharto, Tentiyo; Saidi, Ahmad (LPPM Universitas Bina Insan, 2020)
In making it easier for them in economic activities such as storing funds, investing in banks, sending money, borrowing money, and other activities related to financial problems. Islamic banks are financial institutions that carry out banking activities based on sharia principles. The legal entity form of a Bank carries out its economic activities, humans are assisted by an institution engaged in the financial sector, namely a Bank or other financial institution. Banks that can assist Sharia are Limited Liability Companies that have been regulated in article 7 of Law No. 21 of 2008 concerning Islamic Banking. The principle of murabahah in the practice of Islamic financial institutions is based on two main elements of the purchase price as well as the associated costs and agreement on the profits obtained by the institution. In addition to the legal basis for murabahah is al-Qur'an and also as-sunnah, murabahah is also regulated by an institution that specifically regulates financial institutions related to sharia in Indonesia, namely the National Sharia Council of the Indonesian Ulema Council (DSN-MUI). This type of research is library research. While the nature of this research is descriptive, which describes and describes the problems discussed. Accounts receivable in murabahah is a condition in which a murabahah contract occurs between the customer and Islamic banking. Non-performing financing is something that is not desired by any financial institution, including Islamic banking, whose financing problems in Islamic banking have been grouped based on their collectibility, which are substandard, doubtful and bad. The methods taken in solving the problem of debt and receivables in murabahah according to the DSN fatwa Number 47 of 2005 are silaturrahmi, extension of the period, injection of funds, additional funds, Execution of Collateral and Auctions. In addition to the above methods of solving problem loans, it can also be through legal institutions, in this case the State Receivables Affairs Committee (PUPN) and the Directorate General of State Receivables and Auctions (DJPLN), through the Judiciary, and through Arbitration or Alternative Dispute Resolution Bodies.